2015
DOI: 10.3141/2505-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Adhesion Properties of Asphalt Mixtures with the Use of Bitumen Bond Strength and Surface Energy Measurement Tests

Abstract: The interaction between asphalt binder and aggregate is fundamental to ensure adequate performance of asphalt mixtures, mainly in the presence of water. The work of adhesion generated between both materials directly affects the resistance of asphalt mixture to moisture damage, because it measures the ease with which water can displace asphalt binder from the aggregate surface. The objective of this study was to characterize the bond strength between asphalt and several aggregate sources. A PG 64-22 neat binder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(20 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Polymer modification [46,52,53] • γincreases slightly; [20] • No clear effect on γtotal; [18] • γtotal increases, γLW increases, γ+ decreases, γvaries, γAB decreases; [49] • Increase after RTFOR, reduction after PAV in γtotal, similar trend for LW and basic component, the acidic component increases after each aging step.…”
Section: Sfe Measurement Results On Aggregatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymer modification [46,52,53] • γincreases slightly; [20] • No clear effect on γtotal; [18] • γtotal increases, γLW increases, γ+ decreases, γvaries, γAB decreases; [49] • Increase after RTFOR, reduction after PAV in γtotal, similar trend for LW and basic component, the acidic component increases after each aging step.…”
Section: Sfe Measurement Results On Aggregatesmentioning
confidence: 99%
“…Method to determine surface energies of bituminous binders [18,20,21,23,24,26,[28][29][30][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Wilhelmy plate tests in probe liquids (VCG), ambient [20,39,[48][49][50][51] Sessile drops of probe liquids on bitumen surface (VCG) ambient [18,20,35] Inverse gas chromatography (CVS) [46,52] Pending drop (100-140 • C) combined with sessile drop on PTFE (OW) [53] Sessile drops on a microtome-cut bitumen surface 20 • C (OW) [39,54] Sessile drops of probe liquids on bitumen surface (OW) ambient [55] Dynamic sessile drop measurements of probe liquids on a bitumen surface (VCG) [56] Pending drops of bitumen (100-130 • C) (γ total) [53] Pending drops at equiviscous temperatures (γ total) [57] Pending drops of bitumen at a fixed G* 209 Pa (γ total) [39] Wilhelmy plate tests in probe liquids (OW) ambient [20] Atomic force microscopy (dispersive component)…”
Section: Reference(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that aging affects the adhesion of an asphalt-aggregate system based on the measurements of adhesive bond energy at different aging levels. Depending on the source of binder and aggregates, the adhesion may increase or decrease (Cheng, 2002;Aguiar-Moya et al, 2015;Kassem et al, 2016). Furthermore, aging may change the chemistry of the asphaltaggregate interface of RAP materials, which results in a different adsorption mechanism between asphalt and aggregates.…”
Section: Determination Of Aging Kinetic Parametersmentioning
confidence: 99%